Dashboard System for Predicting Student Practicum Performance Using the Data Mining Method - Adam Fahsyah Nurzaman; Riyanto Jayadi (Universitas Negeri Medan, 2022)
One of the factors that can influence the success of an educational institution is the coveted quality of students. To be able to see the quality of students can be seen from the graduation obtained. One method that can be used to see the percentage of student graduation obtained is data mining. This research was conducted to examine the data assessment process using data mining methods as well as data visualization so that the information generated is better by using the dashboard. Decision tree method was chosen because the results obtained using data sources that create the highest accuracy. Out of this research, it is found that the dashboard which was developed to visualize the data to become more mature information and data assessment using data mining methods has succeeded in making stakeholders get better information and also helps in making better business decisions.